Transport processes in temperature gradients thermal diffusion and soret effect in crystalline solids - Korte, Carsten; Janek, Jürgen; Timm, H.; Justus Liebig University Giessen (My University, 1997)
The redistribution of a mobile component in a mixed conductor of the type A1+deltaXν in a temperature gradient is governed by the ratio of the heat of transport of the mobile component and the thermodynamic factor. Both quantities exhibit extrema at or close to the stoichiometric composition. As a consequence, the resulting thermal segregation factor (ddelta/dT)j=0 shows a strong composition dependence. We present a formal description which allows the prediction of (ddelta/dT)j=0 and discuss experimental results.
Keywords: Transport; Thermal diffusion; Soret effect; Defects; Mixed conductors; ddc:540